Vāstuvidya : oru pa₋layavyākhyānattōṭukūṭiyatȧ - Candṟaśēkharanpiḷḷa, Vi; Bālakrṣṇanāśāri, S. (Tiruvanantapuraṃ Malayāḷagṟanthāvali ;, 1978)
Critical edition of a Sanskrit verse work on ancient Indian architecture.